Role of The State Intelligence Agency in Managing the COVID-19 Pandemic in Indonesia (Jurnal Politik, 2023)
The COVID-19 pandemic has prompted governments in various countries to involve a wide range of actors, including intelligence. Since the beginning of 2020, the State Intelligence Agency (BIN) in Indonesia has been actively involved in dealing with the COVID-19 pandemic. The deployment of intelligence bodies in handling a pandemic is a common practice that many democratic countries do. However, intelligence must operate within the confines of its mandate, function, and democratic principles. This paper will examine the issues regarding the roles of BIN in dealing with the pandemic in Indonesia. Data sources for this study were obtained by applying a qualitative approach from literature studies and reviews from January 2020 to February 2021. This paper has identified four types of operations carried out by BIN on a national and local scale: investigations, security, mobilization, and countermeasures. Apart from the various contributions made by BIN to the pandemic response thus far, this paper identifies several issues, including the tendency for excessive involvement, proportionality issues, and accountability issues. As a recommendation, more efforts are needed to strengthen BIN’s position in general security sector governance, accelerate supervision, and reorient COVID-19 handling in Indonesia.